Nekateri mehanizmi razvijanja bralne pismenosti na področju vzgoje in izobraževanja - Haramija, Dragica (Jezik in slovstvo, 2024)
This article highlights the issue of developing reading literacy in connection with revising the curriculum for kindergartens and curricula across the entire education and training vertical. It draws attention to the role of all professionals in kindergartens and schools in developing reading literacy. It also emphasizes that reading literacy is influenced by the way literacy is taught, quality teaching materials, the motivation of students for reading and appropriate strategies for working with students.
Keywords: bralna motivacija; building blocks of reading; gradniki bralne pismenosti; kindergarten; literacy; ne zaključna dela; opismenjevanje; reading motivation; school; šola; vrtec